Constitutional Court Decision No 169/Puu-Xxii/2024 and Efforts to Mainstream Gender in Political Representation on Parliament: Keputusan Mahkamah Konstitusi Nomor 169/Puu-XXII/2024 dan Upaya Pengarusutamaan Gender dalam Perwakilan Politik di Parlemen - Rahayu, Susi Dian; Arifudin Arifudin (Universitas Negeri Semarang, 2025)
Constitutional Court Decision Number 169/PUU-XXII/2024 is a new chapter in the struggle for gender mainstreaming in Indonesia through a legal approach. This study aims to analyse the significance of this decision as a progressive legal instrument to promote gender equality in legislative institutions. The research method uses normative juridice research. The findings reveal that this decision reconstructs the MD3 Law with two major breakthroughs: first, it reinforces the phrase ‘prioritising women's representation’ at the leadership level of the Council's Organs as an imperative command; second, it requires the proportional distribution of female members throughout the Council's Organs based on the principles of balance and equity. The implications of this ruling structurally transform the political landscape of parliament by preventing the domestication of women and opening up access to participation in all policy areas.